2021
DOI: 10.1088/1755-1315/943/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Indonesian Sustainable Palm Oil (ISPO) Policy in Managing Oil Palm Plantation in Indonesia

Abstract: The purpose of this research is to look at the governance of sustainable oil palm plantation development in Jambi Province through an analysis of the role of the Jambi Provincial Government’s policies in realizing sustainable oil palm plantation management. The study used a qualitative approach to explain current findings on the sustainable development of oil palm plantations in Jambi province. The data in this study used an analysis of Jambi Province policy documents related to the oil palm plantation sector’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, without proper procedures, land clearing can result in environmental damage such as forest and land fires, which contributes to the persistent pollution problem in Riau Province. To grow oil palm plantations sustainably, transparent and effective monitoring and evaluation of social and legal factors must be carried out (38). Therefore, cooperation and collaboration from all stakeholders are needed for sustainable palm oil development.…”
Section: Stakeholder Perceptions In the Existing Condition Of Oil Pal...mentioning
confidence: 99%
“…However, without proper procedures, land clearing can result in environmental damage such as forest and land fires, which contributes to the persistent pollution problem in Riau Province. To grow oil palm plantations sustainably, transparent and effective monitoring and evaluation of social and legal factors must be carried out (38). Therefore, cooperation and collaboration from all stakeholders are needed for sustainable palm oil development.…”
Section: Stakeholder Perceptions In the Existing Condition Of Oil Pal...mentioning
confidence: 99%
“…al [20], found that the European food industry is currently requesting the Roundtable on Sustainable Palm Oil (RSPO) standard, while the European biodiesel industry is seeking International Sustainability and Carbon Certification (ISCC) [20]. Therefore, the Government of Indonesia requires large-scale and small-scale plantation companies to have Indonesian Sustainable Palm Oil (ISPO), where this certification is expected to be a ticket for plantation companies or self-help groups to remain productive without ignoring environmental and social issues in the palm oil industry national and local [21,22]. In addition, the solution that can be taken to overcome the problem of oil palm development is a collaboration between companies that act as the nucleus, and oil palm smallholders as plasma to consistently apply the principles of sustainability.…”
Section: Figure 1 the Problems Of Oil Palm Development In Riau Provincementioning
confidence: 99%
“…In addition, there has been a rise in the amount of money allotted from the Palm Oil Plantation Fund Management Institution to the farmer's palm as a result of the Policy Regulation of the Minister of Agriculture Number 7 of 2019 concerning Human Resource Development, Research and Development, Rejuvenation, and Oil Palm Plantation Facilities and Infrastructure. This in the future will provide institutional strengthening for oil palm smallholders to consciously implement environmentally friendly and sustainable management [21,22]. The various policies described above have emphasized that the government has provided ample space for smallholders and companies to partner in the context of managing sustainable oil palm plantations in Indonesia [29].…”
Section: Sustainable Oil Palm Plantationmentioning
confidence: 99%
“…The peat ecosystem in Jambi Province is in a critical condition of 8.07%, very essential at 18.05%, medium critical at 38.93%, and only 34.95% is in a relatively good state. In addition to being caused by fires, the destruction of peat ecosystems in Province Jambi due to the conversion of plantations and industrial forests also occurs in limited cultivated land [14,15].…”
Section: Figure 1 Peatland Distribution In Indonesiamentioning
confidence: 99%